Estratégias hormonais de indução/sincronização de estro em novilhas de corte entre 12 e 14 meses de idade - Bragança, José Francisco Manta (2007)
of The aim of this study was to develop and evaluate two protocols for estrus synchronization and/or induction in 12-14 months old beef heifers, which would allow the use of timed artificial insemination (TAI) after a short period of estrus detection (48h). The first experiment consisted of evaluating whether eCG was a necessary component in the BioRep system to be used in heifers. To address this question 64 heifers (Bos taurus x Bos indicus) were randomly divided into 2 groups: eCG (treatment n=32) and no eCG (controle n=32). A second experiment was performed with the objective of increasing the number of animals in the eCG group to evaluate the consistency of the results obtained in the first experiment (n=92). On day 0 animals from group treatment received a vaginal pessary containing 250mg of medroxyprogesterone acetate (MPA) for 7 days, along with an intramuscular (IM) injection containing 2.5mg of estradiol benzoate (EB). On day 6 animals were treated with 250IU of eCG (IM) and i~g of cloprostenol sodium in the vulvar submucosa (VSM). After MPA withdrawal heifers were checked for estrus manifestation for 48h and were inseminated 12 hours after estrus detection. Heifers which did not manifest estrus during the 48h observation received i~g of GnRH (IM) and were inseminated 16 to 24h later by TAI. Heifers in the control group received a similar treatment except for the eCG injection which was not used. Because results from treatment group on first and second experiments were not different, pooled conception (55.2%) and pregnancy (46.2%) rates were compared to control rates (23.07% and 25.0% respectively) showing a significant improvement of those rates. We conclude that the use of eCG associated with MPA improves pregnancy rates of 12-14 months old beef heifers. Our second objective was to evaluate the use of progestogens in a system of estrus induction/synchronization using eCG-GnRH-MPA-PGGnRH (eMGPG) in 12-14 months old beef heifers. Bos taurus heifers, mostly Red Angus, were randomly divided into 2 groups: eMGPG (n=85) and eGPG (n=85). Heifers on group eMGPG received 400IU of eCG (IM; day -3) with the objective of inducing an increase in follicular growth, leading to higher responsiveness of follicles to GnRH. Seventy-two hours after eCG injection animals were given GnRH (100g; IM; day 0) and a vaginal pessary containing 250mg of MPA for 7 days. At MPA withdrawal (day 7) 5mg of Dinoprost was injected into the VSM. Fourty-eight hours after pessary withdrawal estrus detection followed by AI was performed. Heifers which did not manifest estrus received 100g of GnRH (IM) and were inseminated 16 to 24h later by TAI. Females from group eGPG received a protocol similar to group eMGPG, except for MPA which was not used. Percentage of estrus manifestation on groups eMGPG and eGPG after prostaglandin injection were 23.5% (20/85) and 22.3% (19/85) respectivelly (p>0.05). Similarly, conception and pregnancy rates on groups eMGPG (65.0%; 13/20 and 37.6%; 32/85%) and eGPG (68.4%; 13/19 and 28.2%; 24/85) were not statistically different. To evaluate the response of follicles with different sizes after eCG administration, 12-14 months old heifers were randomly divided into groups of animals containing follicles of 5.0 (small), 8.5 (medium) and >10.0mm (large) to receive 400IU of eCG (IM) during diestrus. Follicular diameters on day 3 of the control of follicular growth by ultrasound were 13mm, 10mm and 8mm on groups of large, medium and small follicles, respectively. We conclude that the use of eCG prior to the regular hormonal protocol, with the objective of increasing the follicular responsiveness to GnRH does not replace a source of progestagen during the synchronization/induction of estrus in 12-14 months old beef heifers.Furthermore, some females despite the prior administration of eCG depending upon their stage of follicular development do not reach a diameter compatible with GnRH responsiveness